Refractive index sensing using ultrasonically crushed polymer optical fibers. (24th November 2016) - Shimada, Shumpei; Lee, Heeyoung; Shizuka, Makoto; Tanaka, Hiroki; Hayashi, Neisei; Matsumoto, Yukihiro; Tanaka, Yosuke; Nakamura, Hitoshi; Mizuno, Yosuke; Nakamura, Kentaro
Abstract: We demonstrate power-based refractive index (RI) sensing using an ultrasonically crushed polymer optical fiber (POF). This structure can be easily and cost-effectively fabricated within a short time (i.e., ∼1 s) without the need to employ external heat sources or chemicals. The only requirement is to simply press a horn connected to an ultrasonic transducer against part of the POF. The RI dependence of the transmitted power shows linear trends in RI ranges of ∼1.32 to ∼1.36 [coefficient: −62 dB/RIU (RI unit)] and ∼1.40 to ∼1.44 (coefficient: −257 dB/RIU). The temperature dependence of the transmitted power is also investigated.